Electric vehicle smart charging - Vasconcelos, Dino Gonçalves (2020)
In recent years, the number of electric vehicles (EVs) has been increasing. It will play more and more important role in the power grid operation because of its storage features, where charging and discharging control strategies and construction of the charging facilities are the priorities to be solved in this field. At the same time, the availability of the charging infrastructures is still limited and provides a promising application area for communication and control research. This thesis focuses on the control of the energy status offered by the buildings/houses providing a power management across the EV charging session. It also describes the development of a system to dynamically control the charging of EVs and maintain the operation of the power system by knowing the available power. To charge EVs a communication between the EV and the charging station is needed. The communication is based on the standard IEC61851, which specifies a pulse width modulation (PWM) signal that is sent to the EV to define the charging current. The system hardware consists of two modules, a charging station and a coordinator both with communication capabilities, while the power management algorithms are in a server, which then calculates the available power based on the power consumption behaviour and uses it to assign the charge of the EV. The system aims to control the EV charging session considering the power consumption to control their charging current. For the case of multiple EVs, the system will manage the charging session based on a priority level prioritizing the EV how started to charge first. The results shows the feasibility of the charging system approach to control the EV charging station considering the system power consumption and the introduction of the priority level for multiple EVs.